Determinant of Indonesia Government Financial Reporting Quality - Januarti Tiurmaida; Etty Murwaningsari; Binsar Simanjuntak; Sekar Mayangsari (Journal of Business and Management Review, 2021)
This study aims to examine the factors that determine the quality of financial statements in the central government in Indonesia at Ministries/Agencies, namely audit findings and follow-up of audit recommendations. This study uses quantitative methods with secondary data from 74 of 88 Ministries/Agencies in the Central Government in Indonesia. The sampling method is purposive sampling with financial statements starting from 2015-2019 which are processed using the STATA. This study shows that audit findings and follow-up of audit recommendations affect the quality of financial reporting. The more audit findings can have a negative impact on the quality of financial reports and the more follow-up on audit results recommendations can have a positive impact on the quality of financial reporting. This study only analyzes audit findings and follow-up of audit recommendations without any other variables that can support the quality of financial statements and can lead to accuracy in this study. Research is important for the central government in maximizing efforts to maintain the quality of financial reports in the context of accountability to stakeholders, especially to the community through the House of Representatives. This study provides new insights into the factors that determine the quality of central government financial reports in Indonesia.